Optimal Choice of Travelling System Structure depending on Design Parameters of Hoisting System in Drilling Units of Oil and Gas Wells - Hadid, Dr. Mahmoud M.; Mohammed, Ahmed A. (Journal of Petroleum Research and Studies, 2022)
Most drilling rigs are designed based on the max static load on the hook of great travelling system structure as 6×7. But when change the depth of the well, the load on the hook changes, so it was necessary to determine the travelling system structure, which ensures the best design indicators of hoisting system. This research studied the impact of travelling system structure on design parameters of hoisting system and the best indicators of hoisting systems at less drilling lines number suitable with max allowable load on hook for oil and gas wells drilling units. In this work, A methodology depending on graphical solution for hoisting system indicators curves has been developed. (MATLAB) has been used in order to develop a program that facilitates the application of this methodology and accelerate the work. The most important technical parameters for different drilling unit, in addition to the allowable hookload, by using the most important design indicators that positively or negatively affecting the system with changing travelling system structure. This program depending on graphical solution for set of these indicators in relation with number of drilling lines by finding equilibrium point between positive and negative effects that has the algebraic sum of the slopes is as close as possible to zero. This point represent optimal drilling lines compatible with hookload at practical technical parameters for drilling units. This study achieves the best indicators for hoisting system working at ideal travelling system and decrease the time required for drilling by increasing hook velocity rate by 12% and the efficiency of hoisting system by 10%. In addition, the lengths of drilling line rate decreased by 40% that cause reduction in material cost and achieving better economic feasibility in comparison with design travelling system.